PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE EXAMPLES NON EXAMPLES UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 003 BAGAN BATU KECAMATAN BAGAN SINEMBAH - Erman Saputra; Eddy Noviana; Lazim N Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The background in this study is low yields social studies class IV SDN 003 Bagan Batu with a score of 59.75 basis of the average score Minimum Criteria completeness (KKM) social studies is 68 of 40 fourth grade students of SDN 003 Chart Stone. Students who complete 16 while not complete as much as 24. This research is a class action (PTK) is done to boost the results of social studies class IV SDN 003 Bagan Batu by applying models Non Examples Examples cooperative mode. This research is a classroom action research (PTK) which aims to improve student learning outcomes IPS Class IV SDN 003 Chart stone by applying cooperative learning model type Non Examples Examples. Problem formulation in this study is whether the application of learning models cooperative Type Non Examples Examples can improve learning outcomes IPS Class IV SDN 003 Bagan Batu ?. The research was conducted on 16 March 2015 until 13 April 2015 with a study carried out two cycles pembelajaran.Subject this was grade IV SDN 003 Chart stone which numbered 40 student. 18 male students and 20 female students. Data collection instruments in this research activity Sheet Teacher, Student activity sheets and test results belajar.This research presents the results obtained from the score of learning semester. Prior to action with an average value of 59.75 and after the action increased the daily test I in the first cycle to 69.5 and the second daily test cycle II increased to 79.75. While the activities of teachers at the first meeting of the cycle I have nilai16 or 66.66% and the second was a meeting increased to 17 or 70.83% and the second cycle the first meeting was increased activity experienced teachers from grades 18 or 75% to 20 or 83.33% , Results of the study in class IV SDN 003 Bagan Batu proved that the application of cooperative learning model of Type Non Examples Examples can increase hasilk fourth grade of social studies lesson at SDN003 Bagan Batu Kecamatan Bagan Sinembah.Keywords: examples and non Examples, IPS learning Outcome